Correlation Between Urine Albumin Creatinine Ratio (uACR) and the Incident of Acute Kidney Injury in Sepsis Patients - Nedya, Vegha; Arto, Nindia Sugih; Zainumi, Cut Meliza (Universitas Padjadjaran, 2025)
Sepsis is the most common cause of Acute Kidney Injury (AKI). Diagnosis of AKI based on serum creatinine (sCr) has limitations, sCr increases only after >50% kidney function is lost. uACR examination is a simple test to assess microalbuminuria which reflects impaired kidney function. Analyzing the correlation between uACR and AKI incidence in sepsis patients treated at Adam Malik Hospital. The study design was observational analytic with prospective cohort design. Samples were taken consecutively. Sepsis diagnosis was based on qSOFA score. uACR and sCr I were checked <24 hours after sepsis was diagnosed, sCr II was rechecked 48 hours later to assess the occurrence of AKI. Data were analyzed using SPSS. There were 52 study subjects, predominantly male (57,7%), with an average age of 52,5±16,42 years, and the most common source of infection was the lungs (82,7%). AKI occurred in 46,2% of study subjects. The AUC area of uACR as a predictor of AKI was 75,2%. The independent variable that significantly influenced AKI was uACR (p<0,001). The uACR cut-off was 225 mg/g, with a sensitivity of 83,3%, a specificity of 67,9% and an accuracy rate of 75%. uACR levels ≥225 mg/g had a 10,556 times risk of AKI. There is a significant correlation between uACR and the incidence of AKI so it can be used as a predictor of AKI in sepsis patients.Keywords: Acute kidney injury, albuminuria, rasio albumin kreatinin, sepsis.